PREVENTION OPPORTUNITIES FOR THE RESPIRATORY INFECTIONS AMONG CHILDREN WITH THE INSULIN DEPENDENT DIABETES - A.A. Tarasova; M.P. Kostinov; O.N. Volkova; M.S. Deulin; S.V. Suloeva; I.V. Mayanskaya; N.I. Tolkacheva ("Paediatrician" Publishers LLC, 2006)
20 children with the insulin dependent diabetes have been vaccinated with pneumo 23 against pneumococcal infection during the two week prevention course by immunomodulating spray IRS 19. Topical lysate was prescribed on the day of vaccination in the season, immediately preceding the flu epidemy. Before application of topical lysate, as well as in a month and in 3 months after the pre vention course was over, the researchers evaluated the biocenose indices of nasal and fauces cavity mucosa. Alongside, otorhinolaryngologist examined the children. IRS 19 prescription helped to avoid the emergence of intercurrent diseases during the post vaccinal period, in the meantime, it led to the reduction of pathogenic flora sowing, intensity of the inflammatory changes in the nasal pharynx and fauces. Vaccination against pneumococcal infection and combined application of Pneumo 23 with IRS 19 among children with the insulin-dependent diabetes contributed to the reduction of frequency and severity of the respiratory ingections if compared with the similar indices of 43 patients with diabetes, who did not receive immunization.Key words: children, insulin dependent diabetes, chronic tonsillitis, tissue immunity, immunoregulatory spray, vaccine against pneumococcal infection.